Common Tangents

Calculus Level 3

Let n n be a positive integer and

{ f ( x ) = x 2 n + 1 g ( x ) = x 2 n + 1 \large \begin{cases} f(x) = x^{2n + 1} \\ g(x) = \sqrt[2n + 1]x\ \end{cases}

The two curves above have two common tangent lines which are parallel.

(1) Find two linear functions λ ( n ) \lambda(n) and γ ( n ) \gamma(n) for which the distance d d between the two parallel lines above can be expressed as d = λ ( n ) 2 γ ( n ) γ ( n ) λ ( n ) d = \dfrac{\lambda(n)\sqrt{2}}{\gamma(n)^{\frac{\gamma(n)}{\lambda(n)}}} .

(2) Find the value of n n for which γ ( n ) + λ ( n ) = 9 \gamma(n) + \lambda(n) = 9 .

Refer to previous problem:


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 7, 2018

f ( a ) = ( 2 n + 1 ) a 2 n = g ( b ) = 1 ( 2 n + 1 ) b 2 n 2 n + 1 f'(a) = (2n + 1)a^{2n} = g'(b) = \dfrac{1}{(2n + 1)b^{\frac{2n}{2n + 1}}} \implies a = ± 1 α ( n ) b 1 2 n + 1 a = \pm\dfrac{1}{\alpha(n)b^{\frac{1}{2n + 1}}} , where α ( n ) = ( 2 n + 1 ) 1 n \alpha(n) = (2n + 1)^{\frac{1}{n}}

Using a = 1 α ( n ) b 1 2 n + 1 a = -\dfrac{1}{\alpha(n)b^{\frac{1}{2n + 1}}} \implies

A : ( 1 α ( n ) b 1 2 n + 1 , 1 α ( n ) 2 n + 1 b ) A:(-\dfrac{1}{\alpha(n)b^{\frac{1}{2n + 1}}}, -\dfrac{1}{\alpha(n)^{2n + 1}b}) and B : ( b , b 1 2 n + 1 ) B:(b,b^{\frac{1}{2n + 1}})

m A B = ( α ( n ) 2 n + 1 b 2 n + 2 2 n + 1 + 1 α ( n ) b 2 n + 2 2 n + 1 + 1 ) ( 1 α ( n ) 2 n b 2 n 2 n + 1 ) = 1 α ( n ) b 2 n 2 n + 1 α ( n ) n + 1 b 2 ( n + 1 ) 2 n + 1 = 1 b = ( 1 α ( n ) ) 2 n + 1 2 \implies m_{AB} = (\dfrac{\alpha(n)^{2n + 1}b^{\frac{2n + 2}{2n + 1}} + 1}{\alpha(n)b^{\frac{2n + 2}{2n + 1}} + 1})(\dfrac{1}{\alpha(n)^{2n}b^{\frac{2n}{2n + 1}}}) = \dfrac{1}{\alpha(n)b^{\frac{2n}{2n + 1}}} \implies \alpha(n)^{n + 1}b^{\frac{2(n + 1)}{2n + 1}} = 1 \implies b = (\dfrac{1}{\alpha(n)})^{\frac{2n + 1}{2}} \implies a = ( 1 α ( n ) ) 1 2 a = (\dfrac{1}{\alpha(n)})^{\frac{1}{2}}

α ( n ) = ( 2 n + 1 ) 1 n b = 1 ( 2 n + 1 ) 2 n + 1 2 n \alpha(n) = (2n + 1)^{\frac{1}{n}} \implies b = \dfrac{1}{(2n + 1)^{\frac{2n + 1}{2n}}} and a = 1 ( 2 n + 1 ) 1 2 n a = \dfrac{1}{(2n + 1)^{\frac{1}{2n}}}

m A B = g ( b ) = 1 \implies m_{AB} = g'(b) = 1 and A : ( 1 ( 2 n + 1 ) 1 2 n , 1 ( 2 n + 1 ) 2 n + 1 2 n ) A:(-\dfrac{1}{(2n + 1)^{\frac{1}{2n}}},-\dfrac{1}{(2n + 1)^{\frac{2n + 1}{2n}}})

Using the symmetry about the line y = x A ( 1 ( 2 n + 1 ) 2 n + 1 2 n , 1 ( 2 n + 1 ) 1 2 n ) y = x \implies A'(-\dfrac{1}{(2n + 1)^{\frac{2n + 1}{2n}}},-\dfrac{1}{(2n + 1)^{\frac{1}{2n}}})

\implies the distance d = A A = 2 n 2 ( 2 n + 1 ) 2 n + 1 2 n = λ ( n ) 2 γ ( n ) γ ( n ) λ ( n ) d = AA' = \dfrac{2n\sqrt{2}}{(2n + 1)^{\frac{2n + 1}{2n}}} = \dfrac{\lambda(n)\sqrt{2}}{\gamma(n)^{\frac{\gamma(n)}{\lambda(n)}}}

and,

γ ( n ) + λ ( n ) = ( 2 n + 1 ) + ( 2 n ) = 4 n + 1 = 9 n = 2 \gamma(n) + \lambda(n) = (2n + 1) + (2n) = 4n + 1 = 9 \implies n = \boxed{2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...